BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2012)
Role of Resistance in Intensive Agriculture.Editors: S. Nagarajan and D.P. Singh. (ISBN81-7663-888-9) Kalyani Publishers, New Delhi,2001, 261 pp., Rs. 250.00